DAMPAK QUICK RATIO DAN LONG TERM DEBT to EQUITY RATIO TERHADAP NILAI PERUSAHAAN - Hery Pandapotan Silitonga; Robert Tua Siregar; Elly Susanti (JURNAL MUTIARA AKUNTANSI, 2019)
The purpose of this study is to determine the effect of quick ratio (QR) and long term debt to equity ratio (LtDER) on tobacco in cable companies listed on the Indonesia Stock Exchange. The population of this study is the cable sub-sector companies listed on the Indonesia Stock Exchange in the period 2013-2018. Sampling with a purposive sampling method, obtained as many as 5 companies to be sampled. Data analysis techniques used are multiple linear regression, hypothesis testing, correlation coefficient, and coefficient of determination. The results of the quick ratio (QR) research have a negative effect while the long term to debt ratio (LtDER) has a positive effect on tobacco in the Cable Sub Sector Listed on the Indonesia Stock Exchange for the period 2013-2018. This shows that the higher the quick ratio will decrease Tobins'q and the higher the long term debt to equity ratio will increase the Tobins'q obtained.